Peran Partisipasi Perempuan dan Keberhasilan Program Pemberdayaan Agribisnis Jamur Tiram di Desa Karangsari, Kecamatan Sapuran Wonosobo: The Role of Women's Participation and the Success of the Oyster Mushroom Agribusiness Empowerment Program in Karangsari Village, Sapuran District, Wonosobo - Widodo, Aris Slamet; Sriyadi, Sriyadi; Wibisana, Dharend Lingga; Amirullah, Gufron; Qomariyah, Puji; Suseno, Ari; Ulum, Bahrul; Togubu, Randy; Arintoko, Tri Ragil; Saifan, Erik (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to analyze women's participation in the oyster mushroom agribusiness empowerment program and assess the program's success in the Waste Donation Group and Village-Owned Enterprises (BUMDes) of Karangsari Village, Wonosobo. The research method used a case study with a population of 78 members and data were analyzed using a Likert-Richert scale and correlation techniques. The results showed that women's participation was high (total average score of 90.45) with the highest scores in the implementation (24.42) and evaluation (24.38) stages. The program successfully increased members' knowledge, skills, and income (total average score of 26.74), and there was a significant positive relationship between women's participation and program success (r = 0.775; p = 0.00). These findings confirm the role of women as a determinant factor in the success of the community-based agribusiness empowerment program.